Simultaneous magnetic and structural transitions in Nd0.15Ca0.85MnO3 manganite: Magnetization and neutron diffraction studies. (June 2019) - Dhal, Lakshman; Rayaprol, Sudhindra; Morozkin, A.V.; Shukla, N.; Geetha Kumary, T.; Malik, S.K.; Santhosh, P.N.; Nirmala, R.
Abstract: The manganite Nd0.15 Ca0.85 MnO3 crystallizes in GdFeO3 -type, orthorhombic structure (space group Pnma ) at 300 K and orders antiferromagnetically at 112 K (TN ). Magnetization-field (M-H) isotherms indicate metamagnetic transition at temperatures below TN . However, metamagnetism does not lead to saturation in magnetization. The magnetization value at 2 K in 140 kOe field is only 0.4 μB /f.u. The isothermal magnetic entropy change (ΔSm ) has been calculated using the M-H data and inverse magnetocaloric effect is observed around TN and the maximum value of ΔSm is ∼12.2 J kg −1 K −1 at 107.5 K for 140 kOe field change. Powder neutron diffraction study in zero applied field reveals monoclinic distortion of Nd0.15 Ca0.85 MnO3 crystal lattice and antiferromagnetic ordering of Mn sublattice in ac -plane with wave vectorK = [1/2, 0, 1/2] at 125 K. From the neutron data, the Mn magnetic moment value at 3 K is found to be 2.54 μB . Electrical resistivity increases tremendously below TN to an insulating state and shows thermal hysteresis near TN in zero field. Large magnetic fields drive insulator to metal-like transition and negative colossal magnetoresistance of about 70% is realized at 50 K in 70 kOe field and that could be due to the field-induced order. Highlights: Simultaneous magnetic and crystal structural transitions are observed in electron doped Nd0.15 Ca0.85 MnO3 . Inverse magnetocaloric effect occurs in the vicinity of the first order antiferromagnetic transition (TN ). The metamagnetic transition below TN likely drives the colossal magnetoresistance.